4 - A Mulher guineense como sujeito e objecto do debate histórico contemporâneo: Excertos da história de vida de Teodora Inácia Gomes - Gomes, Patrícia Godinho (Africa Development, 2021)
The armed struggle conducted in Guinea-Bissau promoted profound changes in the social formation, particularly in terms of cultural, social and administrative structures (education, health and justice). However, the building of a new society fell far short from the real expectations of the Bissau-Guinean people after the independence. Based on the method of oral History, this study discusses the first results of a wider research on one of the Bissau-Guinean Women figures who embody the practical application of Amilcar Cabral’s thought, Teodora Inácia Gomes. The research make use of some fragments of Teodora’s life history, of the Amilcar Cabral’s discourse on Women condition, of the PAIGC’s documents and of the literature on the subject.